Distal Femoral Focal Deficiency - Soini Venla; Haara Mikko; Raitio Arimatias; Syvänen Johanna (United States, 2025)
Distal femoral focal deficiency is an extremely rare type of congenital femoral deficiency that comprises hypoplasia of the distal femur, with a normally developed hip. We represent a unique case of distal femoral hypoplasia and deficiency of knee extensors, childhood follow-up and final treatment with exarticulation, and a comparison with previous literature.